Analysis of 36 Y-STR marker units including a concordance study among 2085 Dutch males. (January 2015) - Westen, Antoinette A.; Kraaijenbrink, Thirsa; Clarisse, Lindy; Grol, Laurens J.W.; Willemse, Patricia; Zuniga, Sofia B.; Robles de Medina, Elizaveta A.; Schouten, Ron; van der Gaag, Kristiaan J.; Weiler, Natalie E.C.; Kal, Arnoud J.; Kayser, Manfred; et al.
Highlights: All 5 Y-STR multiplexes efficiently generated genotyping data for 2085 Dutch donors. 99.0% of the haplotypes were unique when all 36 Y-STR marker units were combined. 19 Y-STR marker units were present in multiple kits and showed 0.002% discordance. Abstract: The genotypes of 36 Y-chromosomal short tandem repeat (Y-STR) marker units were analysed in a Dutch population sample of 2085 males. Profiling results were compared for several partially overlapping kits, i.e. PowerPlex Y, Yfiler, PowerPlex Y23, and two in-house designed multiplexes with rapidly mutating Y-STRs. Nineteen Y-STR marker units, of which two are rapidly mutating, reside in at least two of these multiplexes, and for these markers concordance testing was performed. Two samples showed discordant genotyping results and the probable causative base change was revealed by Sanger sequencing. In addition, we encountered concordant, but aberrant genotyping results including one allele with low peak height and several null alleles. For 12 samples, this involved a null allele in two adjacent loci suggesting a large and recurrent deletion as the samples represent three distinct haplogroups. For each marker unit, the allele counts and frequencies are presented, as are the haplotype counts and haplotype diversities for several combinations of markers.